2010
DOI: 10.4276/030802210x12892992239116
|View full text |Cite
|
Sign up to set email alerts
|

A Phenomenological Study of Volition in Everyday Occupations of Older People with Dementia

Abstract: Aim: The aim of this study was to understand volition in people with moderate dementia. The study provided an in-depth description and analysis of volition in eight older people in a memory-support assisted living unit.Method: Guiding questions focused on understanding past life interests, demonstration of volition, volitional continuity, and the relationship among the social environment, volition and daily occupations. Data collection included participant observation, family and staff interviews, and the Voli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(65 citation statements)
references
References 9 publications
0
62
0
3
Order By: Relevance
“…An observational study explored the volition for everyday activities (termed occupations) in eight older people with dementia, in an assisted living unit (Raber et al 2010). They concluded that all types of interaction (researcher, staff, and family) had a pervasive impact on the volitional behaviour of those with dementia.…”
Section: Impact Of Positive Social Environments In Dementiamentioning
confidence: 99%
See 1 more Smart Citation
“…An observational study explored the volition for everyday activities (termed occupations) in eight older people with dementia, in an assisted living unit (Raber et al 2010). They concluded that all types of interaction (researcher, staff, and family) had a pervasive impact on the volitional behaviour of those with dementia.…”
Section: Impact Of Positive Social Environments In Dementiamentioning
confidence: 99%
“…They concluded that all types of interaction (researcher, staff, and family) had a pervasive impact on the volitional behaviour of those with dementia. This study highlighted the importance of person-centred, staff interaction, in encouraging residents with interactive and social occupations (Raber et al 2010). However, Yates-Bolton et al (2012) proposed that implementing these findings may be more difficult in acute hospital settings, due to the fast-paced environment, with a lesser focus on social interaction, compared to longer term residential settings.…”
Section: Impact Of Positive Social Environments In Dementiamentioning
confidence: 99%
“…Outras pesquisas não apresentaram uma definição sobre o conceito de cotidiano, mas afirmaram e/ou abordaram sobre a importância da vida cotidiana para uma determinada população ou em um contexto específico (ERIKSSON; THAM; FUGL-MEYER; 2005; WRIGHT-ST CLAIR; KERSE; SMY THE, 2011; HASSELKUS; MURRAY, 2007;RABER et al, 2010;PERSSON;ZINGMARK, 2006;NÄTTERLUND, 2010).…”
Section: Resultsunclassified
“…They highlighted that it is more difficult to assess the "meaningfulness" of occupations with people with more advanced dementia and speculated that occupation might play a more important role in the early stages. Fortunately, evidence stemming from people with dementia themselves is growing, (Han, Radel, McDowd, & Sabata, 2016;Orrell et al, 2008;Raber, Teitelman, Watts, & Kielhofner, 2010), but the perspective of people in the moderate to severe phases has been neglected (Caddell & Clare, 2010). There is, however, some evidence that when occupations are perceived to be irrelevant, people with mild and moderate dementia prefer not to do anything rather than attending organised sessions (Tak, Kedia, Tongumpun, & Hong, 2015).…”
mentioning
confidence: 99%